IMPROVING SPEAKING SKILL USING GROUP DISCUSSION - Melody Daely; Sela Astarini; Hendra Husnussalam (IKIP Siliwangi, 2019)
This article aimed to : (1) describe how small group discussion can be implemented to improving the students speaking ability. (2) To find out wheter there is improvement of students’ speaking ability through small group discussion. This research was conducted by using classroom action research method, and small-group discussion as a technique with 35 students of the nineth grade participating in this research. Classroom action researh consists of 4 cycles, they are : planning, acting, observing and reflecting. In conducting data, the resercher used observation and interview. The result of the studybshowed the students’ score in the cycle 1 on the pre-test it was 57,33, and on the post-tst in cycle 2 it was improved to be 66,67, in the cycle 3 and on post-test it was 70,06. Based on the these results, it can be concluded that small group discussion improve the students’ speaking ability. This research used qualitative research.